All the creatures of the wheel at stake: Re-assessing science, anti-science and religion in The Omega Man. Issue 2 (1st October 2020) - Bigliardi, Stefano
The most significant motifs of Boris Sagal's The Omega Man (1971) have been heavily scrutinized. Critical literature mentions science vs. anti-science as one of the film's themes, yet only occasionally and fragmentarily. I contend that this opposition is central to the movie and that a richer interpretation of it can be reached by taking into account more elements in the movie's action, dialog and imagery than critics have done thus far.